2009
DOI: 10.1177/1545109709343967
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions to Nonnucleoside Reverse Transcriptase Inhibitor-Based Antiretroviral Regimen: A 24-Week Prospective Study

Abstract: As the developing world increasingly uses generic ART, the clinician must be constantly vigilant for treatment-related adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…70 Neuropsychiatric manifestations most commonly associated with EFV use include dizziness, confusion, lethargy, impaired concentration, amnesia, hallucinations, abnormal dreams, insomnia, sleep disorders, depression, and irritability. 71,72 The CNS symptoms usually appear in the first weeks of therapy and abate within several weeks. [73][74][75][76][77] While the exact mechanism responsible for these neuropsychiatric effects by EFV has not been established, some studies suggest that the CNS side effects are related to the higher level of plasma EFV exposure .…”
Section: Neuropsychiatric Effects Of Artmentioning
confidence: 99%
“…70 Neuropsychiatric manifestations most commonly associated with EFV use include dizziness, confusion, lethargy, impaired concentration, amnesia, hallucinations, abnormal dreams, insomnia, sleep disorders, depression, and irritability. 71,72 The CNS symptoms usually appear in the first weeks of therapy and abate within several weeks. [73][74][75][76][77] While the exact mechanism responsible for these neuropsychiatric effects by EFV has not been established, some studies suggest that the CNS side effects are related to the higher level of plasma EFV exposure .…”
Section: Neuropsychiatric Effects Of Artmentioning
confidence: 99%
“…Severe life-threatening hepatotoxicity, including fatal fulminant hepatitis, has also been reported during therapy with NVP. In a recent study of NVP patients, 25.7% developed grade 1 hepatotoxicity and 2.8% displayed severe hepatotoxicity (Jena, 2009). There is also conflicting evidence about the involvement of NVP therapy in the progression of liver fibrosis in patients with a concomitant HCV infection, as some studies support this hypothesis (Macías, 2004) whereas others relate NVP to a reduction of fibrosis (Berenguer, 2008).…”
Section: Hepatotoxicitymentioning
confidence: 86%
“…There is also conflicting evidence about the involvement of NVP therapy in the progression of liver fibrosis in patients with a concomitant HCV infection, as some studies support this hypothesis (Macías, 2004) whereas others relate NVP to a reduction of fibrosis (Berenguer, 2008). Up to 10% of EFV-treated patients exhibit increases of liver enzymes that may require discontinuation of therapy and which have been associated both with hypersensitivity to EFV and dose-dependent accumulative effects (Angel-Moreno-Maroto, 2006;Jena, 2009;Kappelhoff, 2005;Rivero, 2007). In fact, a substudy of the 2NN trial showed a correlation between the incidence of elevated levels of liver enzymes and plasma concentrations of EFV during the first 6 weeks of treatment.…”
Section: Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…4 Although the primary therapeutic goals of ART are to achieve and maintain viral suppression and improve patient immune function, among the secondary goals should be to select a safe and effective regimen, taking into account individual patients, underlying conditions, concomitant medications, and history of drug intolerance. 5 In India, the National AIDS Control Organization (NACO) introduced inexpensive and generic ART drugs. 6 So, with the availability of generic HAART at low cost, an increasing number of HIV-infected individuals in India are now receiving therapy.…”
Section: Growingmentioning
confidence: 99%